Ethnochemistry: Exploring the Potential of Sasak and Java Local Wisdom as a Teaching Materials - Dwi Wahyudiati (Universitas Pendidikan Ganesha, 2022)
The lack of availability of learning resources in the form of teaching materials is one of the problems found in chemistry learning, both in secondary schools and in tertiary institutions, so it is very urgent to develop contextual chemistry teaching materials as an implementation of the ethnochemical approach in learning. The purpose of this study was to explore and develop chemistry teaching materials as learning resources by exploring the potential of local Sasak and Javanese wisdom. This research approach uses a qualitative approach with data collection techniques through literature, interviews, and documentation. The data obtained were analyzed using Miles & Huberman's qualitative analysis. The research subjects consisted of community leaders, chemical content experts, and chemical literature relevant to the research study. Based on the research findings, it can be concluded that Sasak and Javanese local wisdom can be used as a source of chemistry learning through integrating Sasak and Javanese local wisdom with chemical bonding materials and changes in elements, compounds, and mixtures. Thus, the implications of this research can be a source of reference in developing contextual chemistry teaching materials so as to make learning more meaningful.